Ecological risk assessment for difenoconazole in aquatic ecosystems using a web-based interspecies correlation estimation (ICE)-species sensitivity distribution (SSD) model. (February 2022) - Shen, Chao; Pan, Xinglu; Wu, Xiaohu; Xu, Jun; Dong, Fengshou; Zheng, Yongquan
Abstract: Difenoconazole is a typical triazole fungicide that can inhibit demethylation during ergosterol synthesis. Due to its wide use, difenoconazole is frequently detected in surface water, paddy water, agricultural water, and other aquatic environments. Presently, an assessment of the ecological risk posed by difenoconazole in aquatic ecosystems is lacking. Here, a web-based interspecies correlation estimation (ICE)-species sensitivity distribution (SSD) model was first applied to assess the ecological risk of difenoconazole in aquatic environments. Meanwhile, maximum acceptable concentration (MAC), maximum risk-free concentration (MRFC), and risk quotient ( RQ) values were used to evaluate the potential risk of difenoconazole to aquatic organisms. Our results showed that an aquatic MAC value of 0.31 μg/L was acceptable for difenoconazole in aquatic environments. Further, the detected concentration of difenoconazole was lower than the MRFC value of 0.09 μg/L indicating no risk to aquatic organisms. Assessment data suggested that difenoconazole exhibited potential risks to eight studied aquatic ecosystems (including surface water, paddy water, and agricultural water) in different countries ( RQ > 1), indicating that difenoconazole overuse could cause adverse effects to aquatic organisms in these aquatic ecosystems. Thus, restricted use and rational use of difenoconazole are recommended. Graphical abstract: Image 1 Highlights: A Web-based ICE-SSD model was applied to assess the ecological risk of difenoconazole. MAC value for difenoconazole in the aquatic ecosystems was 0.31 μg/L. MRFC value for difenoconazole in the aquatic ecosystems was 0.09 μg/L. Difenoconazole exhibited potential risks to eight detected aquatic ecosystems. Rational or restricted use of difenoconazole are recommended.